MINUM KHAMER MENURUT PERSPEKTIF HUKUM PIDANA ISLAM - Diah Astuti; Nor Halisa; Ranti Sari; Lahmudinur (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
The act of consuming khamer (alcoholic beverages) and the sanctions imposed on the offenders. The research employs a normative juridical approach by examining primary legal sources such as the Qur’an, Hadith, and both classical and contemporary fiqh literatures. The findings indicate that drinking khamer is classified as a jarimah hudud since it is explicitly prohibited in Islamic law. The prohibition aims to protect human intellect (hifz al-‘aql), one of the fundamental objectives of maqāṣid al-syarī‘ah, which safeguards moral and social order. The prescribed had punishment, consisting of forty to eighty lashes, is not merely punitive but also serves educational and preventive purposes. Furthermore, the prohibition carries profound wisdom in promoting a healthy, ethical, and dignified society. This study concludes that Islamic criminal law embodies comprehensive principles of justice and public welfare in maintaining social harmony.